La gestion administrativa y su incidencia en el sistema de crédito del comercial ISRAEL periodo 2011 - 2012 - Bermeo Briones, Maria Leonor (2012)
This analysis allowed to determine a preliminary diagnosis of the formulation is the manner in which commercial operation Israel. The information obtained is based on interviews and observations collective meeting people working in it. This work has to be seen to do all planning and control in regards to the credit system, this was achieved through raised as objects were identified current trade situation, investigate the credit system and to determine the compliance with administrative policies within its system of credit. To achieve compliance with the surveys we help direct employees and the owner, also used the rules needed to be innovative and strategic plans to improve the quality of care and offer new loans.